2019
DOI: 10.1021/jacs.9b09813
|View full text |Cite
|
Sign up to set email alerts
|

Azulene-Derived Fluorescent Probe for Bioimaging: Detection of Reactive Oxygen and Nitrogen Species by Two-Photon Microscopy

Abstract: Two-photon fluorescence microscopy has become an indispensable technique for cellular imaging. Whereas most two-photon fluorescent probes rely on well-known fluorophores, here we report a new fluorophore for bioimaging, namely azulene. A chemodosimeter, comprising a boronate ester receptor motif conjugated to an appropriately substituted azulene, is shown to be an effective two-photon fluorescent probe for reactive oxygen species, showing good cell penetration, high selectivity for peroxynitrite, no cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 117 publications
0
69
0
1
Order By: Relevance
“…•− and • NO (Zielonka et al, 2012b), numerous boronate redox probes were developed and reported for the detection of cellular ONOO − (Yu et al, 2012;Rios et al, 2016;Sedgwick et al, 2017;Murfin et al, 2019;Weber et al, 2020). CBA was also used in combination with the immuno-spin trapping technique to demonstrate ONOO − -mediated protein radical formation in microglial cells exposed to lipopolysaccharide (Kumar et al, 2014).…”
Section: Fluorescence-based Monitoring Of H 2 O 2 and Onoo − Formed Imentioning
confidence: 99%
See 1 more Smart Citation
“…•− and • NO (Zielonka et al, 2012b), numerous boronate redox probes were developed and reported for the detection of cellular ONOO − (Yu et al, 2012;Rios et al, 2016;Sedgwick et al, 2017;Murfin et al, 2019;Weber et al, 2020). CBA was also used in combination with the immuno-spin trapping technique to demonstrate ONOO − -mediated protein radical formation in microglial cells exposed to lipopolysaccharide (Kumar et al, 2014).…”
Section: Fluorescence-based Monitoring Of H 2 O 2 and Onoo − Formed Imentioning
confidence: 99%
“…The CBA probe was used to demonstrate the formation of ONOO − as the product of the reaction of and • NO, when used at different ratios (Zielonka et al, 2010 ) and as a product of the reaction of HNO with O 2 (Smulik et al, 2014 ). Following the CBA- and FlAmBE ( 22 )-based detection of ONOO − in RAW 264.7 macrophages stimulated to coproduce and • NO (Zielonka et al, 2012b ), numerous boronate redox probes were developed and reported for the detection of cellular ONOO − (Yu et al, 2012 ; Kim J. et al, 2014 ; Rios et al, 2016 ; Sedgwick et al, 2017 ; Murfin et al, 2019 ; Weber et al, 2020 ). CBA was also used in combination with the immuno-spin trapping technique to demonstrate ONOO − -mediated protein radical formation in microglial cells exposed to lipopolysaccharide (Kumar et al, 2014 ).…”
Section: Chemical Reactivity Of Boronates Toward Biological Oxidantsmentioning
confidence: 99%
“…This fact has been exploited for its use in a range of colorimetric sensors. Examples include sensors for silver (Wakabayashi et al, 2013), nitrite (Murfin et al, 2020), mercury (Wakabayashi et al, 2007(Wakabayashi et al, , 2008(Wakabayashi et al, , 2012Razus et al, 2011;Birzan et al, 2017;Buica et al, 2018Buica et al, , 2019, phosphate (Lichosyt et al, 2016(Lichosyt et al, , 2018, and reactive oxygen species (Murfin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Murafuji et al demonstrated the synthesis of azulene-substituted cyclic boronic acid esters 156a – 156e by the reaction of 2-azulenylboronic acid 155 with several diols ( Scheme 52 ) [ 73 ]. The reaction of 2-azulenyl lithium 154 with trimethyl borate yields a boronic acid ester, which is then hydrolyzed by acid to give 2-azulenylboronic acid 155 .…”
Section: Synthesis and Reactivity Of Azulene Derivatives With 4- mentioning
confidence: 99%